PENERAPAN E- GOVERNMENT MELALUI APLIKASI DUKCAPIL SMART DI KABUPATEN BANTUL - Fakhrul Umam Hadi; Tri Yuniningsih; Endang Larasati S. (Journal of Public Policy and Management Review, 2023)
Information technology is rapidly developing in many sectors. One of the sector is the government. The Population and Civil Registration Office of Bantul Regency implemented Electronic-Government, the Dukcapil Smart Bantul Application, as an online Population Administration service. However, there are many complaints from the people about its implementation. This study aimed to determine the implementation, the supporting and inhibiting factors of applying the Dukcapil Smart Bantul. The research method used in this research was descriptive qualitative. The results of this study indicated that the Dukcapil Smart Bantul Application had implemented the successful elements of E-Government, such as support, capacity, and value. However, several criteria have not been the standard, such as the quality and quantity of human resources and infrastructure that was not yet adequate. In terms of application, several factors affected the service of this application to its users, based on the theory of E-Government quality, It can be seen that the supporting factors is included user data security, easy application access, clear application display. In contrast, the inhibiting factors of this application included ineffective flow clarity, not yet compatible with all types of smartphones, and a service speed that was not optimal.